1998
DOI: 10.1177/026988119801200306
|View full text |Cite
|
Sign up to set email alerts
|

The nitric oxide synthesis inhibitor L-NAME produces anxiogenic-like effects in the rat elevated plus-maze test, but not in the social interaction test

Abstract: The effects of the nitric oxide synthase inhibitor, Nw-nitro-L-arginine methyl ester (L-NAME) were investigated in two animal models of anxiety: the elevated plus-maze and the social interaction test. In the elevated plus-maze, L-NAME (12.5-50 mg/kg) had an anxiogenic-like profile as indicated by dose-dependent reductions in the time spent on the open arms, open arm entries, the percentage of open arm entries and head dips, but there was no significant effect on the number of stretch attend postures. In contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
21
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 24 publications
5
21
0
Order By: Relevance
“…These results conform with studies of Vale et al (1998) after intraperitoneal (i.p.) injection of L-NAME.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results conform with studies of Vale et al (1998) after intraperitoneal (i.p.) injection of L-NAME.…”
Section: Discussionsupporting
confidence: 91%
“…There is growing evidence that NO is involved in the regulation of anxiety, although some controversial results have been reported. On the one hand, the NOS inhibitor N g -nitro-L-arginine (L-NOARG) abolished the anxiolytic-like effects of NO (Caton et al, 1994) as well as of chlordiazepoxide (Quock and Nguyen, 1992), and the NOS inhibitor N w -nitro-L-arginine methyl ester (L-NAME) produced anxiogenic-like effects in the rat elevated plusmaze (Vale et al, 1998). On the other hand, an anxiolyticlike action of L-NAME has also been reported in the same model (Volke et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the NO donor detanonoate mimicked the anxiolytic effects of diazepam in the three behavioral tests, whereas the NOS inhibitor L-NAME produced behavioral effects similar to those observed after restraint stress. These effects of NO donors and inhibitors are consistent with the results of earlier studies (De Oliveira et al, 1997;Vale et al, 1998;Monzón et al, 2001;Masood et al, 2003).…”
Section: Downloaded Fromsupporting
confidence: 91%
“…A number of research groups have indeed reported that suppression of NO production can induce anxiogenic-like behavior in a variety of animal models of experimental anxiety Vale et al, 1998;Monzon et al, 2001;Pokk and Vali, 2002;Czech et al, 2003). That NO is involved in reduction of anxiety is supported by the observation that administration of the NO donor 3-morpholinosyndnonimine (SIN-1) evoked an anxiolytic-like response in mice in the light/dark exploration test (Li and Quock, 2002).…”
Section: Discussionmentioning
confidence: 99%